Extreme Depletion of PIP3 Accompanies the Increased Life Span and Stress Tolerance of PI3K-null C. elegans Mutants - Bharill, Puneet; Ayyadevara, Srinivas; Alla, Ramani; Shmookler Reis, Robert J. (Frontiers in Genetics, 2013)
The regulation of animal longevity shows remarkable plasticity, in that a variety of genetic lesions are able to extend lifespan by as much as 10-fold. Such studies have implicated several key signaling pathways that must normally limit longevity, since their disruption prolongs life. Little is known, however, about the proximal effectors of aging on which these pathways are presumed to converge, and to date, no pharmacologic agents even approach the life-extending effects of genetic mutation. In the present study, we have sought to define the downstream consequences of age-1 nonsense mutations, which confer 10-fold life extension to the nematode Caenorhabditis elegans – the largest effect documented for any single mutation. Such mutations insert a premature stop codon upstream of the catalytic domain of the AGE-1/p110α subunit of class-I PI3K. As expected, we do not detect class-I PI3K (and based on our sensitivity, it constitutes <14% of wild-type levels), nor do we find any PI3K activity as judged by immunodetection of phosphorylated AKT, which strongly requires PIP3 for activation by upstream kinases, or immunodetection of its product, PIP3. In the latter case, the upper 95%-confidence limit for PIP3 is 1.4% of the wild-type level. We tested a variety of commercially available PI3K inhibitors, as well as three phosphatidylinositol analogs (PIAs) that are most active in inhibiting AKT activation, for effects on longevity and survival of oxidative stress. Of these, GDC-0941, PIA6, and PIA24 (each at 1 or 10 μM) extended lifespan by 7–14%, while PIAs 6, 12, and 24 (at 1 or 10 μM) increased survival time in 5 mM peroxide by 12–52%. These effects may have been conferred by insulinlike signaling, since a reporter regulated by the DAF-16/FOXO transcription factor, SOD-3::GFP, was stimulated by these PIAs in the same rank order (PIA24 > PIA6 > PIA12) as lifespan. A second reporter, PEPCK::GFP, was equally activated (∼40%) by all three.